Narrativas sobre o ensino de Matemática, em especial de Geometria, no ensino médio da Educação de Jovens e Adultos EJA - Adauto Lucio Auarek (2022)
This work aimed to elaborate understandings about the teaching of Mathematics, especially in the content of Geometry, in high school education of Young people and adults (EJA). To this end, interviews were conducted with five teachers who worked or worked in the EJA in high school, trying to analyze the conceptions evidenced by these subjects about the profile of young and adult students and teaching to this audience; on mathematics in this modality of basic education; and on the teaching of Geometry in general. The research was conducted during the Covid 19 pandemic period and, due to the restrictions imposed, the interviews were conducted at a distance. From these interviews, narratives were elaborated using oral history as a theoretical and methodological framework and it was intended to make analyses according to theoretical references of high school mathematics and JaS. The objective was to bring elements to foster the discussion about the teaching of Mathematics and, in particular, geometry in high school, in the EJA modality. In the interviews, subjects emerged that were common among the reports, such as: the youthization of the students; the difficulty of teaching with the age difference between students; the lack of knowledge of the students for the content of Geometry; the little contact that teachers had with the content of Geometry in their school education; the difficulty of reconciling the curriculum with the EJA modality; and the conditions that school administrations impose regarding the distribution of classes and support to the teacher's work. As an educational product, an e-book was developed that contains a theoretical part on the teaching of Mathematics, especially geometry in high school of the EJA, the narratives of the interviewees and also the analyses and reflections of these practices under the light of the theoretical framework. Keywords: Mathematics and Geometry Education. Education of Young and Adult People. Middle school. Oral history